PYROLYSIS OF ULIN (Eusideroxylon zwageri) SAWDUST IN THE PRESENCE OF NI/SBA-15 USING A PYROLYSIS-GAS CHROMATOGRAPHY-MASS SPECTROSCOPY (PY-GC/MS) - Marsella, Yuni; Subagyono, R. R Dirgarini J.N.; Gunawan, Rahmat (PROSIDING SEMINAR KIMIA, 2023)
Pyrolysis study of Ulin (Eusideroxylon zwageri) sawdust in the presence of Ni/SBA-15 using a pyrolysis-gas chromatography-mass spectroscopy (Py-GC/MS) instrument has been carried out. This study aims to determine the chemical composition of pyrolysis products of Ulin sawdust after the addition of Ni/SBA-15 catalyst. Pyrolysis was carried out at 350, 450 and 550 ºC under helium (He) gas. Based on the percent area of the pyrolysis product identified on the pyrogram, the product of lignin derivatives before the addition of the Ni/SBA-15 catalyst was 58.53-68.14% and after the addition of the Ni/SBA-15 catalyst decreased to 51.08-58.33%. While the cellulose/hemicellulose derivative products before the addition of the Ni/SBA-15 catalyst were 15.62-17.78% and after the addition of the Ni/SBA-15 catalyst increased to 18.91-25.79%. Ulin sawdust catalyzed pyrolysis produced compounds with the highest area percent, namely catechol, isoelemicin, 2-Methoxy-4-vinylphenol, 1,6-anhydro-beta-D-Glucopyranose, and hydroxy-acetaldehyde. Keywords: pyrolysis, Eusideroxylon zwageri, Py-GC/MS, Ni/SBA-15 catalyst